Enhancing growth and physiological traits in alfalfa by alleviating salt stress through biochar, hydrogel, and biofertilizer applications - Jabborova, Dilfuza; Zhang, Yu; Alhewairini, Saleh S.; Jabbarov, Zafarjon; Barasarathi, Jayanthi; Abdrakhmanov, Tokhtasin; Imomov, Otamurod; Abdusamatov, Sokhibjon; Saharan, Baljeet Singh; Sayyed, Riyaz (Frontiers in Microbiology, 2025)
IntroductionSalinity is a significant abiotic stress that affects the growth, physiology, and yield of crop plants across the globe. Sustainable measures to mitigate saline soil and prevent yield losses require immediate attention. The present study aimed to determine the impacts of hydrogel, biochar, and biofertilizer on alfalfa growth and physiological properties under salt stress.MethodsThe experiment was performed in a randomized block design with three replications on the dried bottom of the Aral Sea, consisting of control (T1), hydrogel alone (T2), biochar alone (T3), and biofertilizer alone (T4). Plant growth parameters, root morphological traits, and physiological properties were analyzed after 60 days of sowing.ResultsThe results showed significant improvement in shoot length, shoot dry weight, and root dry weight in biochar alone (T3) and biofertilizer alone (T4) treated plants compared to control (T1) and hydrogel (T2). However, the application of biochar alone (T3) exhibited more pronounced effects compared to other treatments.DiscussionBiochar treatment resulted in the highest chlorophyll a and total chlorophyll contents under salt stress. Soil amendments with biochar, hydrogel, and biofertilizer promote alfalfa growth and yield and help mitigate the adverse impact of salt stress.